Democratic deficit in the European Union between rhetoric and hermeneutics - Szymczyński, Tomasz R. (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2017)
Multidimensionality and dynamics of the European integration process generate almost continuous requirement for adaptation and improvement of its understanding. The situation remains similar in reference to the specific inspection(s) of this process known as a democratic deficit in the European Union. This concept at its general level consists of two highly ambiguous labels: democracy and European Union. On the one hand, the concept of democracy with its almost two and half thousand years of history may be easily presented as a typical “umbrella term” with plenty of strong connotations and lack of one clear unequivocal denotation. On the other hand, the notion of European Union perhaps only seems to be less controversial. The foremost source of ambiguities in this respect comes from the fact, that the concept of the EU is directly connected with the notion of supranationality – fundamental idea functioning as a basis for specificity of European integration process, which may be interpreted as a source of constant challenges of a definitional character both for theoreticians and practitioners of the process. Problems with defining crucial aspects of the European integration process lead to problems of an identity kind. In other words, definitional and identificational challenges maintain in a strong mutual interdependence. In this case hermeneutical point of view helps to set in order this complex matter by proposing the list of issues directly connected with the challenge of adequate interpretation of it. Additionally, the rhetorical aspect of such a challenge is incorporated into the proposed perspective.

Wielowymiarowość i dynamika procesu integracji europejskiej generują niemal ciągły wymóg adaptacji i podwyższania jakości jego rozumienia. Nie inaczej wygląda sytuacja w odniesieniu do konkretnego oglądu tego procesu, który określany jest mianem deficytu demokratycznego w Unii Europejskiej. Ta koncepcja na poziomie ogólnym składa się z dwóch wysoce niejednoznacznych etykiet: demokracja i Unia Europejska. Z jednej strony, pojęcie demokracji z prawie dwoma i pół tysiącami lat historii można łatwo przedstawić jako typowy „parasolowy termin” z dużą ilością silnych konotacji i brakiem jednoznacznej denotacji. Z drugiej strony, pojęcie Unii Europejskiej okazuje się niemniej kontrowersyjne. Najważniejszym źródłem niejasności w tym względzie jest fakt, że kategoria UE jest bezpośrednio związana z pojęciem supranarodowości – zasadniczą ideą funkcjonującą jako podstawa specyfiki procesu integracji europejskiej, którą można interpretować jako źródło stałych wyzwania o charakterze definicyjnym zarówno dla teoretyków, jak i praktyków tego procesu. Problemy z określeniem kluczowych aspektów procesu integracji europejskiej prowadzą do problemów o charakterze identyfikacyjnym. Innymi słowy, wyzwań definicyjne i identyfikacyjne pozostają w silnej wzajemnej zależności. W tym przypadku hermeneutyczny punkt widzenia pomaga uporządkować to złożone zagadnienie proponując listę kwestii bezpośrednio związanych z wyzwaniem adekwatnej interpretacji tego zagadnienia. Dodatkowo, retoryczny wymiar tego wyzwania został uwzględniony w ramach zaproponowanego ujęcia.
Deficyt demokratyczny w Unii Europejskiej między retoryką i hermeneutyką
Keywords: democratic deficit in the EU; supranationality; Hans-Georg Gadamer; rhetoric; hermeneutics of multilinguisticality; deficyt demokratyczny w UE; supranarodowość; Hans-Georg Gadamer; retoryka; hermeneutyka wielojęzykowości